Komunikasi Interaksi Simbolik Spoke Person Badja Coffee Dalam Meningkatkan Brand Awareness Lokalate - Amalia Syafira Effendy; Almira Shabrina (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2024)
The inevitable evolution of consumer needs drives companies, particularly in the Fast Moving Consumer Goods (FMCG) sector, to continuously seek innovation to enhance competitiveness and have a long-term impact on consumers' lives. Often, these innovations are introduced through events. In this context, the importance of the speaker or spokesperson role as a communicator in building trust and conveying messages to the audience is crucial. This research employs a qualitative case study method, focusing on the "Ngopinspirasi" event conducted by PT Nutrifood Indonesia for the Lokalate brand at Nutrihub Bandung, with the increasing awareness among students. The analysis centers on the application of symbolic interaction communication by the micro-business Badja Coffee as a spokesperson during the event to enhance Lokalate awareness at Nutrihub Bandung. The study utilizes Mead's symbolic interaction theory, encompassing three concepts: mind, self, and society. The research subjects the owner of Badja Coffee as the spokesperson and the marketing team of PT Nutrifood Indonesia in Bandung. The findings indicate that interaction communication flows smoothly, harmoniously, with involvement building a close relationship between the spokesperson and the audience. The study also applies Mead's symbolic interaction theory to analyze symbols of the spokesperson's behavior, such as clothing and speech.